The role of the gut microbiome in cardiovascular disease - Świątko, Mateusz; Sosnowski, Paweł; Rybak, Joanna; Grzebyk, Marcin; Tokarska, Anna; Arnista, Aleksandra; Gawrońska, Katarzyna; Waszczuk, Agnieszka; Kołodziejczyk, Aleksandra; Łapiński, Piotr (Journal of Education, Health and Sport, 2025)
In recent years, the gut microbiome has gained increasing recognition as a crucial modulator of physiological homeostasis, including cardiovascular function. Numerous studies indicate that disruptions in the composition and activity of intestinal microbiota—referred to as dysbiosis—may significantly contribute to the onset and progression of cardiovascular diseases, including atherosclerosis, hypertension, heart failure, and arrhythmias. Particular attention has been paid to microbial metabolites such as trimethylamine-N-oxide (TMAO), short-chain fatty acids (SCFAs), and lipopolysaccharides (LPS), which exert significant effects on inflammatory, immunological, and metabolic pathways. The aim of this review was to synthesize current evidence regarding the association between the gut microbiota and the pathogenesis of cardiovascular disorders, emphasizing potential molecular mechanisms and therapeutic opportunities arising from microbiome modulation. Additionally, environmental, dietary, and pharmacological factors influencing microbiota composition and their implications for cardiovascular risk were discussed. Accumulated evidence suggests the gut microbiome could serve both as a biomarker of cardiovascular risk and as a potential therapeutic target within personalized medicine frameworks. However, further clinical research is required to precisely define its role in the pathogenesis and treatment of cardiovascular diseases.